Dinamika Komitmen dan Perilaku Organisasi dalam Mendorong Kinerja Pegawai pada Kantor Dinas Perhubungan Provinsi Kalimantan Timur - Mohammad Rayani; Achmad Fauzi; Eunike Claudia Pingkan Hetharia; Sahan Rizandi; Mitha Virgina Rusady (Dinasti Review, 2024)
This study aims to investigate the dynamics of the correlation between employee commitment to performance, the organizational behavior implications on employee performance, and the combined implications of commitment and organizational behavior on employee performance in Dinas Perhubungan Provinsi Kalimantan Timur. The study method used is quantitative with hypothesis testing to identify determinations between variables. Regression analysis is used to understand the variations, directions, and determinations between independent variables (commitment and organizational behavior) and dependent variables (employee performance). The study was conducted on all employees in Dinas Perhubungan Provinsi Kalimantan Timur using simple random sampling technique. The study results interpret that commitment to employee performance and organizational behavior significantly influence employee performance, and both have a significant determination on employee performance in the office.